2020
DOI: 10.1186/s12889-019-8124-z
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination in healthcare as a barrier to care: experiences of socially disadvantaged populations in France from a nationally representative survey

Abstract: Background: People in socially disadvantaged groups face a myriad of challenges to their health. Discrimination, based on group status such as gender, immigration generation, race/ethnicity, or religion, are a well-documented health challenge. However, less is known about experiences of discrimination specifically within healthcare settings, and how it may act as a barrier to healthcare. Methods: Using data from a nationally representative survey of France (N = 21,761) with an oversample of immigrants, we exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
88
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(93 citation statements)
references
References 43 publications
3
88
1
1
Order By: Relevance
“…In addition to possible differences in health needs, preferences, and expectations different barriers to the utilization of preventive care have been discussed a potential explanation for differences in utilization [13][14][15]. This includes the absent or limited health insurance coverage, language barriers, discrimination and insufficient information about and access to preventive care among migrant population [16,17]. However, many studies have demonstrated that the use of preventive care is generally associated with a medium and high SES [5,18].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to possible differences in health needs, preferences, and expectations different barriers to the utilization of preventive care have been discussed a potential explanation for differences in utilization [13][14][15]. This includes the absent or limited health insurance coverage, language barriers, discrimination and insufficient information about and access to preventive care among migrant population [16,17]. However, many studies have demonstrated that the use of preventive care is generally associated with a medium and high SES [5,18].…”
Section: Introductionmentioning
confidence: 99%
“…patients with chronic conditions such as cancer or diabetes or requiring surgical interventions [12,13]. Discrimination in healthcare can be based on several characteristics, such as income, education, occupation, gender, race, ethnicity or religion and is a welldocumented challenge to equal access in healthcare [14][15][16]. For example, patients with lower socioeconomic status consistently report more discrimination compared to patients with high socioeconomic status.…”
Section: Introductionmentioning
confidence: 99%
“…Data from a variety of studies suggest that erosion of trust in the health care system, due to discrimination and fears of detention and deportation, is resulting in adverse health outcomes among immigrants (D’Alonzo et al., 2020; Novak, Geronimus, & Martinez‐Cardoso, 2017; Szaflarski & Bauldry, 2019; Torres et al., 2018). In addition, immigrants are more likely to report instances of health care discrimination (Hacker, Anies, Folb, & Zallman, 2015; Rivenbark & Ichou, 2020). Nurses are often on the front lines in these confrontations.…”
Section: Introductionmentioning
confidence: 99%